2011
DOI: 10.1001/archinternmed.2011.277
|View full text |Cite
|
Sign up to set email alerts
|

Activity Energy Expenditure and Incident Cognitive Impairment in Older Adults

Abstract: Introduction Studies suggest that physically active people have reduced risk of incident cognitive impairment in late life. However, these studies are limited by reliance on subjective self-reports of physical activity, which only moderately correlate to objective measures and often exclude activity not readily quantifiable by frequency and duration. The objective of this study was to investigate the relationship between activity energy expenditure (AEE), an objective measure of total activity, and incidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
85
3
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(100 citation statements)
references
References 43 publications
7
85
3
5
Order By: Relevance
“…that activity level would be related to both physical and cognitive tasks, as previous research has shown that lower objectively measured activity is related to cognitive impairment (21). However, among the individual tasks, we only found significant associations with tasks that were physical in nature.…”
Section: Discussioncontrasting
confidence: 63%
“…that activity level would be related to both physical and cognitive tasks, as previous research has shown that lower objectively measured activity is related to cognitive impairment (21). However, among the individual tasks, we only found significant associations with tasks that were physical in nature.…”
Section: Discussioncontrasting
confidence: 63%
“…In the 197 men and women tested, a reassessment 2-5 years after baseline showed a significant dose response between energy expenditure and the later incidence of cognitive impairment. 21 A decline in cognitive function is one of the hallmark symptoms of AD and dementia. While both epidemiological and interventional studies have examined the influence of physical activity or exercise on cognition, a decline in cognition does not necessarily result in dementia and/or AD.…”
Section: Evidence From Epidemiological Studiesmentioning
confidence: 99%
“…Prior studies have shown associations between LTPA and cognitive performance, [2][3][4][5][6][7][8] and a recent meta-analysis 9 has demonstrated a dose-response association between LTPA and subsequent risk of dementia. These studies tend to show a protective effect on only vascular dementia or on Alzheimer disease alone.…”
mentioning
confidence: 98%